Do Not Respond! Doing the Think/No-Think and Go/No-Go Tasks Concurrently Leads to Memory Impairment of Unpleasant Items during Later Recall - Herbert, Cornelia; Sütterlin, Stefan (Frontiers in Psychology, 2012)
Previous research using neuroimaging methods proposed a link between mechanisms controlling motor response inhibition and suppression of unwanted memories. The present study investigated this hypothesis behaviorally by combining the think-no-think paradigm (TNT) with a go/no-go motor inhibition task. Participants first learned unpleasant cue-target pairs. Cue words were then presented as go or no-go items in the TNT. Participants’ task was to respond to the cues and think of the target word aloud or to inhibit their response to the cue and the target word from coming to mind. Cued recall assessed immediately after the TNT revealed reduced recall performance for no-go targets compared to go targets or baseline cues, not presented in the TNT. The results demonstrate that doing the no-think and no-go task concurrently leads to memory suppression of unpleasant items during later recall. Results are discussed in line with recent empirical research and theoretical positions.